We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
64
1
avatar+153 

deleted

 Sep 29, 2019
edited by SoulSlayer615  Oct 23, 2019

Best Answer 

 #1
avatar+6045 
+1

\(\text{Subtract 3 times the first equation from the second}\\ -16y = 48\\ y=-3\\ x+3(-3)=-4\\ x = 5\\~\\ (x,y)=(5,-3)\)

.
 Sep 29, 2019
edited by Rom  Sep 30, 2019
 #1
avatar+6045 
+1
Best Answer

\(\text{Subtract 3 times the first equation from the second}\\ -16y = 48\\ y=-3\\ x+3(-3)=-4\\ x = 5\\~\\ (x,y)=(5,-3)\)

Rom Sep 29, 2019
edited by Rom  Sep 30, 2019

7 Online Users